PL 480 aid and India's food problem - Shenoy, Bellikoth Raghunath, 1908- (Artha Niti Publications series., 1974)
Critique of the supply of American surplus agricultural commodities to India under the Agriculture trade and assistance act of 1954 (PL 480) of the U.S. Government.